Universities in translation : the mental labor of globalization - Bary, Brett de, 1943- (Traces (Ithaca, N.Y.) ;, 2010)
Essays analyze the global movement to "reform" and standardize higher education as a translation of disciplinary technologies of new managerialism from business and industry to the university.